2008
DOI: 10.4161/cc.7.8.5740
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol: A multitargeted agent for age-associated chronic diseases

Abstract: Extensive research within the last decade has revealed that most chronic illnesses such as cancer, cardiovascular and pulmonary diseases, neurological diseases, diabetes, and autoimmune diseases exhibit dysregulation of multiple cell signaling pathways that have been linked to inflammation. Thus mono-targeted therapies developed for the last two decades for these diseases have proven to be unsafe, ineffective and expensive. Although fruits and vegetables are regarded to have therapeutic potential against chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
339
1
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(354 citation statements)
references
References 120 publications
4
339
1
3
Order By: Relevance
“…In fact, RSV prevents or delays the onset of age-related diseases, such as diabetes, inflammation, Alzheimer's disease and CVD, also inducing neuroprotection and inhibiting neoplastic growth (69)(70)(71)(72)(73)(74)(75)(76)(77) . The therapeutic potential of RSV has been demonstrated by the extended lifespan and ameliorated motor function in mice fed a high-energy diet (78) .…”
Section: Rsv (34mentioning
confidence: 99%
“…In fact, RSV prevents or delays the onset of age-related diseases, such as diabetes, inflammation, Alzheimer's disease and CVD, also inducing neuroprotection and inhibiting neoplastic growth (69)(70)(71)(72)(73)(74)(75)(76)(77) . The therapeutic potential of RSV has been demonstrated by the extended lifespan and ameliorated motor function in mice fed a high-energy diet (78) .…”
Section: Rsv (34mentioning
confidence: 99%
“…More than 20 epidemiologic surveys have consistently showed that common non-steroidal anti-inflammatory drugs may protect against the development of AD (Rogers, 2008) and, although mono-targeted therapies have proven so far ineffective in preventing AD, new agents that block several cellular pathways simultaneously are being analyzed (Harikumar and Aggarwal, 2008). It seems that amyloid-b peptide, which is derived from the longer amyloid precursor protein (APP), is the main stimulator of the inflammatory response found in the brain of AD patients (Sastre et al, 2008), resulting in the presence of activated microglia and astrocytes around neuritic plaques (Rodrigo et al, 2004) and increased levels of inflammatory mediators (Hoozemans et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The major RSV dietary sources are shown in Figure 1. This metabolite was initially recognized as an antibiotic produced in response to various environmental stresses, such as mechanical damage, microbial infection, UV radiation, heat, and pathogenic conditions (Harikumar & Aggarwal, 2008; Pervaiz, 2003). It was initially extracted from the roots of white hellebore ( veratrum grandiflorum O. Loes .)…”
Section: Introductionmentioning
confidence: 99%